Budd–Chiari Syndrome with Patent Hepatic Veins on Imaging: Clinicoradiological Spectrum of Small Vessel Occlusion and Partial Thrombosis of Large Veins - Sasidharan, Rajesh; Suryavanshi, Shubham; Baby, Akhil; Thomas, Sunitha; Philips, Cyriac Abby (Journal of Clinical Interventional Radiology ISVIR, 2025)
Budd–Chiari Syndrome (BCS) usually involves thrombosis or obstruction of major hepatic veins. However, a subset of patients can present with atypical features where hepatic veins appear patent on imaging. The authors present three such cases demonstrating either exclusive small hepatic vein involvement (SHV-BCS) or partial thrombosis of large veins. Despite patent hepatic veins on imaging, patients exhibited features of portal hypertension, with definitive diagnosis established via hepatic venography and transjugular liver biopsy. Two patients responded well to transjugular intrahepatic portosystemic shunt procedure with resolution of ascites, while one was managed conservatively. These cases underscore the diagnostic challenges posed by SHV-BCS and partial thrombosis of large hepatic veins and emphasize the importance of high clinical suspicion and invasive diagnostics in atypical presentations. Early recognition is crucial for timely intervention and favorable outcomes.
Keywords: Budd–Chiari syndrome; small vessel occlusion; hepatic veins